The use of Xitsonga at the University of Limpopo Turfloop Campus : A sociolinguistics analysis - Nkhwashu, Delina (University of Limpopo (Turfloop Campus), 2011)
This study examines the effectiveness and relevance of Xitsonga at the University of Limpopo, Turfloop Campus. The study argues that as one of the six (6) official languages of Limpopo Province, Xitsonga deserves to be treated with the respect that it deserves. Although Xitsonga enjoys some recognition and support nationally and on campus, the study has discovered that there are problems associated with negative attitudes among Xitsonga speakers as they feel that the use of the English language enables them to be part of a global world. Furthermore, a major stumbling block with regard to the use of Xitsonga at the University of Limpopo Turfloop Campus is that some of its speakers hold a negative attitude towards their language as they prefer the use of English language for academic purposes. This is one reason English is still dominant amongst the student community as it is viewed as the language of the corporate world. However, the study reveals that a large number of respondents now support the idea that Xitsonga should be used in all official communication. Finally, the study recommends the use of Xitsonga in social and educational settings. It also recommends the holding of workshops and cultural activities in order to further promote and revitalise the language and its people, thus widening the circle of its acceptance at the Turfloop Campus of the University of Limpopo and beyond.
Thesis (M.A. (Linguistics)) --University of Limpopo, 2011
Keywords: Xitsonga; Sociolinguistics analysis; 496.39780711; Linguistic minorities -- South Africa; Language and education -- South Africa; Tsonga language -- South Africa